Performance and memory in televisional expressions - Cardoso Filho, Jorge Cunha (2017)
This article proposes to understand how constitutive aspects of performances and memory operate in television productions that are built in the interface with popular music. From the performance studies and with analytical emphasis on the text-context relationship, we discuss how issues related to information discourse and fable making as a current pattern of narrative construction based on the analysis of excerpts from the Ensaio program, broadcast by TV Cultura since the 1990s and the Jornal da MTV, which was screened between 2002 and 2007 by the extinct MTV Brasil. These patterns contribute to the production of a provisional contextual stability of the products and, in this sense, also contribute to the construction and perpetuation of memory.